HISTORICAL ASPECTS OF THE SPREAD OF WHEAT IN EUROPE AND UKRAINE AND THE ROLE OF SCIENTIFIC AND RESEARCH INSTITUTIONS IN ITS INTRODUCTION INTO AGRICULTURAL PRODUCTION (INNOVATIVE ECONOMY, 2026)
Kovalyshyn N.M.  HISTORICAL ASPECTS OF THE SPREAD OF WHEAT IN EUROPE AND UKRAINE AND THE ROLE OF SCIENTIFIC AND RESEARCH INSTITUTIONS IN ITS INTRODUCTION INTO AGRICULTURAL PRODUCTIONPurpose. The aim of the article is to study the peculiarities of the spread of wheat in the practice of agricultural management in Europe and Ukraine. To assess the role of scientific and research institutions and, in particular, the Ternopil State Agricultural Research Station of the IAP of the Carpathian region of the NAAS in this process.Methodology of research. The theoretical and methodological basis of the study is a systematic approach to considering phenomena and processes in a historical aspect, using the results of research by Ukrainian and foreign authors devoted to the issues of the spread and introduction of wheat as a crop into agricultural production in Ukraine and Europe. To achieve the goal and obtain the results of the study, a number of general scientific, historical and special research methods were used: monographic – for studying literary sources on the topic under study; induction and deduction – for searching, systematizing and processing the necessary information; logical – for generalizing the entire process in the theoretical form of regularities; historical methods (chronological, synchronous, periodization, retrospective, structural and systematic) – for studying phenomena in space and time; tabular and graphical – for a visual presentation of systematized information; abstract and logical and generalization – for forming conclusions and proposals from the conducted research.  Findings. The main historical periods of the spread and introduction of wheat into agricultural production in Ukraine and Europe are identified. The role of the main breeding centres and research institutions in the development of winter wheat varieties and their distribution, in improving crop cultivation technologies in changing climate conditions is determined. The current state of winter wheat varietal resources in Ukraine is assessed, the share of foreign selection varieties in national agricultural production is determined. A comparative analysis of the qualitative characteristics and varietal features of various varieties of domestic and foreign selections is carried out, the advantages of traditional and modern varieties in terms of yield, ecological plasticity, adaptability, and resistance to stressful environmental conditions are substantiated. The dynamics of winter wheat and spring wheat yields in the agricultural sector of Ukraine in recent years are analysed, and attention is focused on the features of the use of individual technological techniques in wheat cultivation to achieve maximum realization of the potential productivity of varieties in conditions of economic and agro climatic challenges.Originality. Research of the evolution of the introduction of wheat into agricultural production and the role of breeding scientific and research institutions in this process has been further developed.Practical value. The use of the research results will contribute to the further involvement of domestic and foreign varieties of winter wheat in the breeding process of creating new highly productive, environmentally plastic, resistant to stressful environmental conditions varieties in the conditions of climate change, their distribution and use in agricultural production in Ukraine and Europe.Key words: winter wheat, spring wheat, variety, breeding, agricultural technologies, adaptability, biotic and abiotic factors.
Keywords: winter wheat; spring wheat; variety; breeding; agricultural technologies; adaptability; biotic and abiotic factors